Metformin use associated with lower risk of cancer in patients with diabetes mellitus type 2 - Jasna Kusturica; Aida Kulo Ćesić; Edis Gušić; Sanita Maleškić; Maida Rakanović-Todić; Damir Šečić (Medicinski glasnik, 2017)
Aim: In order to increase the database related to the antineoplastic potential of metformin, association between the use of metformin and risk of cancer occurence in patients with diabetes mellitus type 2 (DM2) was investigated. Methods: In this cross-sectional study, medical records of patients with DM2 were reviewed for cancer occurence. Data on age, body mass index (BMI), alcohol and nicotine consumption, glucose and HbA1c levels, duration of DM2, medication used in the treatment of DM2 and cancer occurence were collected and analyzed. Unpaired Student's t-test or Mann-Whitney U test were used for comparisons between treatment groups, and logistic regression to asses how well our set of predictor variables predicts occurence of carcinoma. P-value less than 0.05 was considered statistically significant. Results: The mean age of 234 included patients was 66.8±11.5 years, and DM2 duration was 7± 6.49 years. Mean glucose value was 8.51±4.17mmol/L, and HbA1c 7.74±1.53. Metformin therapy was prescribed in 190 (81%) patients. Cancer was diagnosed in 16 (6.8%) patients: prostate cancer in eight (3.4%), breast cancer in four (1.7%), rectal cancer in two (0.9%) and cancer of the uterus and cervix in one patient. Age, duration of DM2 and BMI did not contribute significantly to the model, while metformin use was shown to be a significant independent predictor (OR=0.049; 95% CI=0.013-0.181; p=0.001). Conclusion: Our findings support the hypothesis that the use of metformin compared to the use of other oral antidiabetic drugs is associated with a lower risk of cancer in patients with DM2.
Keywords: hypoglycemic agents; type 2 diabetes; neoplasms